Structure–function aspects of the Porphyromonas gingivalis tyrosine kinase Ptk1. (25th September 2016) - Liu, C.; Miller, D.P.; Wang, Y.; Merchant, M.; Lamont, R.J.
Summary: The development of synergistically pathogenic communities of Porphyromonas gingivalis and Streptococcus gordonii is controlled by a tyrosine‐phosphorylation‐dependent signaling pathway in P. gingivalis . The Ptk1 bacterial tyrosine (BY) kinase of P. gingivalis is required for maximal community development and for the production of extracellular polysaccharide. We show that the consensus BY kinase Walker A and B domains, the RK cluster, and the YC domain of Ptk1 are necessary for autophosphorylation and for substrate phosphorylation. Mass spectrometry showed that six tyrosine residues in a 16‐amino‐acid C‐terminal region were phosphorylated in recombinant (r) Ptk1. Complementation of a ptk1 mutant with the wild‐type ptk1 allele in trans restored community development between P. gingivalis and S. gordonii, and extracellular polysaccharide production by P. gingivalis . In contrast, complementation of Δ ptk1 with ptk1 containing a mutation in the Walker A domain failed to restore community development or extracellular polysaccharide production. rPtk1 was capable of phosphorylating the tyrosine phosphatase Ltp1 and the transcriptional regulator CdhR, both of which are involved in the development of P. gingivalis communities with S. gordonii .